Respuesta :

Start with out given statement:

Line KM bisects <JKL and the reason for that is because it's given.

For statement 2, we know that m<JKM = m<MKL

because of the definition of an angle bisector.

For statement 3, we can use the angle addition

postulate to get m<JKM + m<MKL = m<JKL.

For statement 4, we use substitution from

the info in statement 2 to get m<MKL + m<MKL = m<JKL.

For statement 5, we simplify to get 2(m < KML) = m<JKL.

For statement 5, we use the division property of equality.

All the reasons are underlined.